Glimepiride Treatment Upon Reperfusion Limits Infarct Size via the phosphatidylinositol 3-Kinase/Akt Pathway in Rabbit Hearts - Hirofumi Nishida; Toshiaki Sato; Momoko Nomura; Masaru Miyazaki; Haruaki Nakaya (Elsevier, 2009)
The phenomenon termed postconditioning, that is, brief episodes of ischemia/reperfusion at the onset of reperfusion reduce infarct size, is thought to involve the activation of the phosphatidylinositol 3-kinase (PI3K)/Akt pathway. Treatment with a drug activating PI3K at the onset of reperfusion may confer a similar cardioprotection. The sulfonylurea glimepiride has been shown to activate PI3K in human endothelial cells. We therefore tested in rabbit hearts whether glimepiride can produce postconditioning-mimetic actions. Langendorff-perfused rabbit hearts were subjected to 30 min of global ischemia and 120 min of reperfusion, and infarct size was determined by triphenyltetrazolium staining. Phosphorylation of Akt was analyzed by Western blotting. Glimepiride (10 μM) treatment for the first 10 min of reperfusion significantly reduced infarct size from 67.2 ± 1.3% in controls to 35.8 ± 4.5% (P<0.01). This infarct size-limiting effect of glimepiride was abolished by a selective inhibitor of PI3K (5 μM LY294002, 65.4 ± 3.4%). Phosphorylation of the PI3K substrate Akt was significantly increased in glimepiride-treated hearts when compared to controls (P<0.05). Glimepiride-induced Akt phosphorylation was inhibited by LY294002. In conclusion, our study demonstrates that glimepiride treatment upon reperfusion reduces infarct size in rabbit hearts via a PI3K/Akt-mediated pathway. The postconditioning-mimetic action of glimepiride may be beneficial for the treatment of diabetic patients with ischemic heart disease. Keywords:: cardioprotection, diabetes mellitus, glimepiride, postconditioning, phosphatidylinositol 3-kinase